1993
DOI: 10.1029/92jb02912
|View full text |Cite
|
Sign up to set email alerts
|

A paleomagnetic study of Tertiary formations from the Kyrgyz Tien‐Shan and its tectonic implications

Abstract: As part of a general investigation of Cenozoic deformation in Central Asia, we studied the paleomagnetism of Tertiary red beds and lava flows from intermontane basins in the Tien‐Shan region of Kyrgyzstan. We collected 532 cores and hand samples from 78 sites at 12 localities and progressively demagnetized them, thermally or with alternating fields. For most sites, there are magnetic components with unblocking temperatures higher than 600°C. We infer that the magnetic carriers are mainly hematite and magnetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 28 publications
9
66
0
Order By: Relevance
“…As shown in Fig. 9, this mean Oligo-Miocene pole for Tarim-Turfan is not statistically different from three Paleogene to early Miocene poles derived from Issyk Kul, Naryn, and Manas in the intramontane basins, or at the northern margin, of the Tian Shan (Chen et al 1991;Thomas et al 1993). Hence no significant rotations are detected between these Paleogene to Miocene results and the 5-50 Ma mean pole for Eurasia (Besse and Courtillot 2002), or from the mean Miocene pole for North China (Huang et al 2004), or from a mid-Miocene pole from volcanic rocks at the northern margin of the Junggar Basin (Huang et al 2006a).…”
Section: Neotectonic Rotation Patterns In the Kashi Depression Westementioning
confidence: 73%
See 2 more Smart Citations
“…As shown in Fig. 9, this mean Oligo-Miocene pole for Tarim-Turfan is not statistically different from three Paleogene to early Miocene poles derived from Issyk Kul, Naryn, and Manas in the intramontane basins, or at the northern margin, of the Tian Shan (Chen et al 1991;Thomas et al 1993). Hence no significant rotations are detected between these Paleogene to Miocene results and the 5-50 Ma mean pole for Eurasia (Besse and Courtillot 2002), or from the mean Miocene pole for North China (Huang et al 2004), or from a mid-Miocene pole from volcanic rocks at the northern margin of the Junggar Basin (Huang et al 2006a).…”
Section: Neotectonic Rotation Patterns In the Kashi Depression Westementioning
confidence: 73%
“…9). We also observe that the paleomagnetic poles obtained from Eocene to Neogene rocks in the Kashi depression and the mean Oligo-Miocene pole for TarimTurfan, as well as those from the Issyk Kul, Naryn, and Manas basins in the Tian Shan (Chen et al 1991;Thomas et al 1993) are distributed along small circles centered about the sampling sites in Tarim-Turfan (Fig. 9).…”
Section: Neotectonic Rotation Patterns In the Kashi Depression Westementioning
confidence: 83%
See 1 more Smart Citation
“…The Fergana basin is an east-west-trending intermontane basin filled with up to 8 km of Cenozoic sediments situated in the southwestern part of the Tien Shan (Bazhenov 1993;Thomas et al 1993;Cobbold et al 1996). The Tien Shan mountain belts stretch Figure 1 Map of Central Asia.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Particularly, none of the events proximal to the Talas-Fergana fault show strike-slip mechanisms, suggesting that this fault is currently locked and that the present-day activity is being accommodated along the neighboring compressional structures (Ghose et al 1998;Xu et al 2006). Paleomagnetic studies concluded that the Fergana basin and the neighboring Chatkal Range have rotated 20°to 30°counterclockwise relative to Eurasia since the Paleocene (Bazhenov 1993;Thomas et al 1993). The results of the work of Zubovich et al (2010), analyzing the regional surface velocity field using GPS data, corroborate the inference that this basin might currently still rotate.…”
Section: Previous Investigationsmentioning
confidence: 99%